Grameen Replicators: Do they reach the poor, and are they sustainable? - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1998)
The Grameen Bank of Bangladesh is widely considered as one of the world's most successful financial institutions banking with the poor. In an effort to alleviate poverty, donors have supported replication programs in 26 countries. This analysis is based on some case studies from Indonesia, the Philippines and Nepal; no comprehensive evaluation has been available. The biggest obstacle in the development of Grameen-type microfinance institutions (MFIs) was found to be donor support: a powerful incentive to substitute external resources for domestic and local savings. This has undermined the institutions' viability and sustainability. As long as they are not self-reliant, they do not reach the poor in sufficient numbers. The Grameen approach is no magic formula, and no best practice or optimal solution that may be applied around the world. However, it incorporates a number of sound practices which may explain some of its success: * high moral commitment of leaders based on values enforced through training; * peer selection and peer enforcement, which preclude adverse selection and moral hazard; * rigidly enforced credit discipline. It further appears that the most promising Grameen-type MFIs are innovators who have modified the classical replication model: * local bank status (rather than NGO or national bank status) * deposit mobilization through differentiated products with attractive interest rates * differentiated loan and insurance products which cover all costs and risks * client differentiation through larger-size loan and deposit products for non-poor members. Some of these practices may be recommended for emulation (not replication!), both by Grameen and non-Grameen MFIs. There is no reason why a Grameen-type MFI registered as a bank which mobilizes its own resources through differentiated savings products, offers cost-effective loan and insurance products and provides larger-size loan and deposit products to non-poor members should not become viable and self-reliant, offering sustainable financial services to an ever-growing number of poor, and eventually non-poor, clients.
Keywords: 330; Informeller Finanzsektor; Armutspolitik; Wirtschaftspolitische Wirkungsanalyse; Asien